Exploring the First-generation College-going Experience - Holliday , Chrissy; Anderson, Sharon K. (Journal of Social Science Studies, 2022)
College-going culture represents the development of college aspiration within individuals, including the necessary guidance and support to prepare students for college. First-generation students, those whose parents have no bachelor’s degree, are of particular research interest because they have lower college-going rates than their peers whose parents have degrees. This reality contributes to disparate educational outcomes with both individual and societal impacts. This mixed-methods case study provides insight into the college-going experiences of first-generation college students by answering the research question, “How did first-generation students attending an Hispanic-serving institution (HSI) experience the phenomenon of college-going culture in their high schools and communities?” Data analysis resulted in six assertions with implications for practitioners and future researchers, including the importance of relationships with high school staff and the opportunity to take dual-enrollment courses.